Long-wavelength monolithic gaInNAs vertical-cavity optical amplifiers - Clark, Antony H. (2009)
We report on the continuous-wave amplification characteristics of an optically pumped 1.3-μm multiple-quantum-well GaInNAs-GaAs vertical-cavity semiconductor optical amplifier (VCSOA). The VCSOA structure was monolithically grown by molecular beam epitaxy and operated in reflection mode in a fiber-coupled system. The maximum on-chip gain attained, limited by the onset of laser action, was 15.6 dB at 196 mW of 980-nm pump power. For a chip gain of 10.4 dB, the optical bandwidth was 10.8 GHz and the saturation output power was -9 dBm. By varying the pump laser power, a maximum extinction ratio of 22.3 dB was obtained. Temperature-controlled tuneable operation of the device is also presented and demonstration of 9 dB of chip gain obtained over 9.5 nm with an optical bandwidth of 12 GHz is reported.